Effects of Two Types of 9-Month Adapted Physical Activity Program on Muscle Mass, Muscle Strength, and Balance in Moderate Sarcopenic Older Women. (18th October 2018) - Piastra, G.; Perasso, L.; Lucarini, S.; Monacelli, F.; Bisio, A.; Ferrando, V.; Gallamini, M.; Faelli, E.; Ruggeri, P.
Abstract : The present study aimed to evaluate the effects of two types of 9-month adapted physical activity (APA) program, based on a muscle reinforcement training and a postural training, respectively, on muscle mass, muscle strength, and static balance in moderate sarcopenic older women. The diagnosis of sarcopenia was done in accordance with measurable variables and cut-off points suggested by the European Working Group on Sarcopenia in Older People (EWGSOP). Seventy-two participants were randomly assigned to two groups: the muscle reinforcement training group (RESISTANCE) (n=35; 69.9 ± 2.7 years) and the postural training group (POSTURAL) (n=37; 70.0±2.8 years). Body composition, muscle mass, skeletal muscle mass index (SMI), and handgrip strength (HGS) were evaluated for sarcopenia assessment, whereas Sway Path, Sway Area, Stay Time, and Spatial Distance were evaluated for static balance assessment. Sixty-six participants completed the study (RESISTANCE group: n=33; POSTURAL group: n=33). Significant increases of muscle mass, SMI, and handgrip strength values were found in the RESISTANCE group, after muscle reinforcement program. No significant differences appeared in the POSTURAL group, after postural training. Furthermore, RESISTANCE group showed significant improvements in static balance parameters, whereas no significant differences appeared in the POSTURAL group. On the whole, the results of this study suggest that the APA program based on muscle reinforcement applied on moderate sarcopenic older women was able to significantly improve muscle mass and muscle strength, and it was also more effective than the applied postural protocol in determining positive effects on static balance.